Regulatory Mechanisms and Clinical Applications of the Long Non-coding RNA PVT1 in Cancer Treatment - Li, Meng-Yuan; Tang, Xiao-Huan; Fu, Yan; Wang, Tie-Jun; Zhu, Jia-Ming (Frontiers in Oncology, 2019)
Cancer is the second leading cause of death worldwide, and no obvious decline in incidence and mortality has occurred in recent years. It is imperative to further investigate the mechanisms underlying tumor progression. Long noncoding RNAs have received considerable attention in recent years because of their major regulatory roles in gene expression. Among them, PVT1 is well-studied, and substantial evidence indicates that PVT1 plays critical roles in the onset and development of cancers. Normally, PVT1 acts as an oncogenic factor by promoting cancer cell proliferation, invasion, metastasis and drug resistance. Herein, we summarize current knowledge regarding the regulatory effects of PVT1 in cancer progression, as well as the related underlying mechanisms, such as interaction with Myc, modulation of miRNAs, and regulation of gene transcription and protein expression. In extracellular fluid, PVT1 mainly promotes cancer initiation, and it normally enhances cellular cancer characteristics in the cytoplasm and cell nucleus. Regarding clinical applications, its role in drug resistance and its potential use as a diagnostic and prognostic marker have received increasing attention. We hope that this review will contribute to a better understanding of the regulatory role of PVT1 in cancer progression, paving the way for the development of PVT1-based therapeutic approaches in cancer treatment.